2017
DOI: 10.1039/c7cc06278h
|View full text |Cite
|
Sign up to set email alerts
|

A Mn-doped Ni2P nanosheet array: an efficient and durable hydrogen evolution reaction electrocatalyst in alkaline media

Abstract: Developing earth-abundant and high-performance electrocatalysts toward the alkaline hydrogen evolution reaction (HER) is highly desired. In this communication, we report a Mn-doped NiP nanosheet array on nickel foam (Mn-NiP/NF) as a high-efficiency electrocatalyst for the HER in alkaline solutions. This Mn-NiP/NF can drive 20 mA cm at an overpotential of 103 mV in 1.0 M KOH, which is 82 mV less than that for NiP/NF. In addition, it also demonstrates excellent long-term electrochemical durability for at least 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(127 citation statements)
references
References 35 publications
2
125
0
Order By: Relevance
“…In contrast, the BEs of Ni 2p 3/2 and Ni 2p 1/2 in Ni‐S−P NRs hybrid are positive‐shifted to 856.7 eV and 874.3 eV, respectively. The characteristic peaks at BEs of 853.1 eV and 870.1 eV in Ni‐S−P NRs/NF can be attributed to the characteristics of Ni δ+ in Ni 2 P ,,. As shown in Figure c and d, the BEs for S 2p 3/2 and S 2p 1/2 in Ni‐S−P NRs/NF exhibit a negative‐shift compared to that of Ni−S/NF, while the BEs of P 2p show a positive‐shift compared to that of Ni−P/NF.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, the BEs of Ni 2p 3/2 and Ni 2p 1/2 in Ni‐S−P NRs hybrid are positive‐shifted to 856.7 eV and 874.3 eV, respectively. The characteristic peaks at BEs of 853.1 eV and 870.1 eV in Ni‐S−P NRs/NF can be attributed to the characteristics of Ni δ+ in Ni 2 P ,,. As shown in Figure c and d, the BEs for S 2p 3/2 and S 2p 1/2 in Ni‐S−P NRs/NF exhibit a negative‐shift compared to that of Ni−S/NF, while the BEs of P 2p show a positive‐shift compared to that of Ni−P/NF.…”
Section: Resultsmentioning
confidence: 84%
“…In recent years, it was found that the Ni‐based compounds could also act as efficient HER electrocatalysts, including Ni‐based sulfides,, nitrides,, phosphides,, etc. Among them, some Ni‐based compounds possess metallic or conductive property, such as Ni 3 S 2 and Ni 2 P, have received special attention ,. The good conductivity allows a fluent charge transfer in the catalysts which is very important for the electrocatalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, heteroatom doping has demonstrated as one of most effective ways to enhance the intrinsic catalytic activity of TMPs by modulating their electronic conductivity and electronic structures . For example, Sun and coworkers presented that Mn‐doped Ni 2 P nanosheets show enhanced HER performance in alkaline electrolyte, which is due to the Mn doping can remarkably improve the electronic conductivity of Ni 2 P. Lu et al reported that Ni‐doped FeP/C hollow nanorods show improved catalytic activity in pH‐universal electrolytes. Density functional theory (DFT) calculation further suggests that the enhanced catalytic activity for HER benefits from the synergistic modulation of the electronic properties and active components.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristic of doping and the structure of the spectrum for Mn, the peaks at 641.7 eV (Mn 2p 3/2 ) could be attributed to Mn 2+ species . The 643.5 eV could be assigned to Mn 2p 3/2 energy losses . The O 1s region (Figure S4 f) shows two peaks located at 531.6 and 532.4 eV, which could be attributed to the P−O bond in the phosphate species and −OH species absorbed on the surface of the PMFCP nanosheets, respectively …”
Section: Resultsmentioning
confidence: 99%